FORMULATION AND OPTIMIZATION OF MUCOADHESIVE MICROSPHERES OF VALSARTAN BY USING BOX-BEHNKEN DESIGN - LAL, CHIMAN; GARG, RAJEEV; GUPTA, GHANSHYAM DAS (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of this study was to formulate and optimize mucoadhesive microspheres of antihypertensive drug (valsartan) within ethyl cellulose as a carrier polymer and carbopol 934P as a mucoadhesive polymer for controlling the release of valsartan. Methods: The emulsion solvent evaporation technique was used for preparation of microspheres of valsartan and the Box-Behnken design was employed with thee independent variables that is amount of ethyl cellulose (X1) and amount of carbopol 934P (X2) and stirring speed (X3) and evaluate four dependent variables such as percentage mucoadhesion, Q1 h, t90% and drug entrapment efficiency. Results: The optimum conditions were found to be X1= 200 mg, X2= 107 mg and X3= 1200rpm. The optimized batch exhibited a high drug entrapment efficiency of 85.63±1.384%, percentage mucoadhesion was 66.76±0.986% and drug release was also sustained for more than 12 h. Conclusion: The analysis of variance showed a significant effect of independent variables. The scaning electron microscopy (SEM) analysis showed that the microspheres were spherical and free-flowing. The microspheres of valsartan were stable after thee month stability study at accelerated condition.